Tourism as an Engine of Wealth Creation in Zimbabwe - Abel, Sanderson; LeRoux, Pierre (International Journal of Economics and Financial Issues, 2017)
Tourism is one of the fastest growing industries in the world. Its rapid expansion has been considered as an interesting possibility for sustainable development including poverty reduction in many countries. Its importance as a growth driver derives from its potential towards exploitation of economies of scale, relieving the foreign exchange constraint, raising efficiency through increased competition, promoting the diffusion of technical knowledge, as an important source of income, employment and wealth. The Zimbabwean tourism sector which has been identified as one of pillars of economic growth in the Medium term Plan (2012-2015) has undergone tremendous changes over the year. These changes reveal that the tourism sector in the country has some form of resilience to challenges that may affect other economic sectors. The study evaluates the major factors underpinning the resilience of the tourism sector and its contribution to the broader macroeconomic aggregates in comparison to the other economic indicators. A descriptive approach is used in the study to describe the data and characteristics of the tourism sector. This methodology is employed when researchers wants to gain a better understanding of a topic, and involve documentary review and descriptive data analysis to explain the phenomena. A comparative analysis was done with other regional countries to determine the position of the sector in the region and also to draw lessons from those countries with a view of proffering solutions on how the industry can spur growth and economic development in the country. Keywords: Tourism, Wealth Creation, Descriptive Approach JEL Classifications: A12, L83